Virulence assessment of Australian Pyrenophora tritici-repentis isolates - See, Pao Theen; Chen, Kefei; Marathamuthu, Kalai; Wood, Blake; Schultz, Nikki; Shankar, Manisha; Moffat, Caroline (2021)
The virulence of 57 Australian isolates of Pyrenophora tritici-repentis (Ptr), a necrotrophic fungal pathogen responsible for the major wheat disease tan spot, was assessed through plant infection assays. Isolates collected from the northern, southern, and western wheat-cropping regions of Australia were evaluated against 16 Australian bread wheat cultivars under controlled growth conditions. Following infection, the wheat panel displayed varying disease symptoms ranging from tiny necrotic specks to spreading chlorotic and necrotic lesions. Analysis of variance indicated that the wheat cultivar exhibited a greater effect on the disease response, explaining 62.7% of the variation, in comparison to the isolate (10.4%). The interaction between the cultivar and the isolate was statistically significant and was attributed to 9.8% of the total variation. All Ptr isolates examined were able to cause disease, but did not display a clear distinction in virulence on the wheat panel investigated, instead showing subtle differences in aggressiveness. Based on the disease responses, there was no obvious pattern between isolate aggressiveness and cropping region. Some cultivars, such as Hydra, exhibited an effective level of resistance in relation to the panel of isolates tested. All 57 Ptr isolates were found to possess the ToxA effector gene and lack the ToxB effector gene. The gene expression level of ToxA was up-regulated at 3 days postinfection in both ToxA-sensitive and -insensitive cultivars, independent of ToxA–Tsn1 recognition.